Development of An Intelligence Street Light Using Fuzzy Logic in Control System - Ahmad Shadli, Ahmad Afiq; Hanafi, Dirman (Evolution in Electrical and Electronic Engineering, 2020)
This paper focused on the energy saving by controlling the light intensity of street light according to the street condition which be measured by the sensor such as light dependent resistor (LDR), passive infrared sensor (PIR), and rain sensor module. LDR detects the natural light intensity which are low, medium, high light intensity. PIR sensor detects the movement of vehicle on the street while the rain sensor module detected the weather at variation phase of water drops (rain) as a safety purpose. In this project, the light intensity of street light is controlled using a functional controller known as the fuzzy logic controller. This type of controller is not based on the model but based on the power detection mechanism. The functional of the system simulates using Proteus Software. The results show the rectangular sinusoidal of the limit of street light intensity.